A multilevel approach to understanding the relationship between entrepreneurship and the urban environment: Empirical evidence from Colombia; Un enfoque multinivel para comprender la relación entre la intención empresarial y el entorno urbano: evidencia empírica para Colombia - Juan Aristizábal; Edwin Tarapuez; Mario Eduardo Hidalgo Villota (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
This document explores the relationship between the structure of cities and entrepreneurial intention EI, supporting empirical evidence of the incidence of exogenous regional factors on business activities. From a sample of Master Business Administration (MBA) students in fourteen cities in Colombia, EI is studied in an urban setting using a two-level binary logistic regression with random intercepts. The purpose of this document is to show empirical evidence for Colombia of the influence of the urban structure on entrepreneurial intention EI, disaggregating hard and soft factors and controlling the initial endowments of a sample of MBA students. At the individual level, EI is driven by gender, age and the presence of family entrepreneurs. In relation to the educational level of the fathers, the EI of the students is not being influenced by the academic training of the mothers. In the same way, our results suggest that the approximate urban structure of cities through hard and soft amenities stimulates EI in MBA students.Our results suppose systematic evidence in order to adapt the business ecosystem to the form and urban conditions of the main cities in Colombia.
Keywords: L26; O18; J24; 330; entrepreneurship; amenities; hard factors; soft factors; Colombia